Lean construction : knowledge and barriers in implementing into Malaysia construction industry - Lim, Victor Aik Jin (2008)
Construction industry is a very fragmented industry and reluctant to accept changes to its current practice because of the belief that construction industry is completely different in nature resulting in producing high wastage and low productivity. Hence, improvement methods or philosophy had been developed out to overcome the above mention problem such as lean construction. Lean Construction is a philosophy based on the concepts of lean production which is termed on 1990 by Womack. Thus, this research was carried out to identify the level of knowledge of local practitioners’ and compare the potential barriers in implementation of lean construction in Industrialised Building System (IBS) and Conventional type of construction. With the help of Statistical Package for Social Sciences Software (SPSS 15.0) and Microsoft Excel, data collected from questionnaire surveys were analysed. In general, local practitioners’ knowledge on lean construction was high, the only problem was most of them (respondents) do not understand the technical term of lean construction yet, applying its principles in their work site. Three potential barriers identified which most of the respondent agreed that it occurred very frequently on site which is (1) Ineffective management practices (Traditional), (2) Just-in-time (JIT) delivery of materials on site (IBS) and (3) "Cut and Paste" from previous project (Traditional and IBS). Statistical test using Wilcoxon Signed- Rank Test shows significant difference between the potential barriers in Traditional and IBS type of construction.